The Effect Of Stock Price, Stock Liquidity And Trading Volume On Stock Split On Companies Listed On IDX In 2015-2020 - Yuliana, Maya; Kinasih , Dwi Dewisri; Sulistyandari , Sulistyandari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine and analyze the effect of stock prices, stock liquidity, and trading volume on stock splits in companies listed on the IDX in 2015-2020. This research is a quantitative research with research sampling method using purposive sampling method . The data analysis method in this study used logistic regression analysis with the help of SPSS 16.0 software. The sample used is 41 companies during the 2015-2020 period. The source of data used in this research is secondary data in the form of the company's annual financial report. The results showed that partially the stock price variable had no significant positive effect on the stock split . The stock liquidity variable partially has a significant positive effect on the stock split . The stock trading volume variable partially has no significant negative effect on the stock split .